Coping with delusions in schizophrenia and affective disorder with psychotic symptoms: the relationship between coping strategies and dimensions of delusion - Rückl, Sarah; Senger, Nana Christina; Büche, Liesa; Backenstraß, Matthias; Barthel, Andreas; Vedder, Helmut; Bürgy, Martin; Kronmüller, Klaus-Thomas (Psychopathology, 2015)
Background: Self-generated coping strategies and the enhancement of coping strategies are effective in the treatment of psychotic symptoms. Evaluating these strategies can be of clinical interest to develop better coping enhancement therapies. Cognitive models consider delusions as multidimensional phenomena. Using a psychometric approach, the relationship between coping and the dimensions of delusion were examined. Methods: Thirty schizophrenia spectrum patients with delusions and 29 patients with affective disorder with psychotic symptoms were interviewed using the Heidelberg Coping Scales for Delusions and the Heidelberg Profile of Delusional Experience. Analyses of variance were conducted to investigate differences between the groups, and Spearman's rank-based correlations were used to examine the correlations between coping factors and the dimensions of delusion. Results: Schizophrenia spectrum patients used more medical care and symptomatic coping, whereas patients with affective disorder engaged in more depressive coping. In the schizophrenia spectrum sample, the action-oriented, the cognitive, and the emotional dimensions of delusion were related to coping factors. In patients with affective disorder, only the action-oriented dimension was related to coping factors. Conclusion: Patients with schizophrenia and affective disorder cope differently with delusions. The dimensions of delusion are related to coping and should be regarded when using cognitive therapy approaches to enhance coping strategies.